Fast acting antimicrobial surfaces and methods of making and using the same
By adopting a biphasic structure in the antimicrobial coating, using materials such as non-fluorinated carbon-based polymers and fluorinated polymers to form a solid structural phase, and dispersing antimicrobial agents such as quaternary ammonium salts are achieved, rapid transmission and high efficiency are achieved Inactivated solves the problems of slow speed and insufficient water resistance of existing coatings.
Patent Information
- Application Number
- CN202080104405.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-06
- Filing Date
- 2020-11-07
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-11-07
AI Technical Summary
Existing antimicrobial coatings kill bacteria and viruses on the surface slowly, making it difficult to achieve an inactivation rate of 99.9 wt% or higher in a short time, and the single material coating is insufficient to swell the water, resulting in the coating. Weakening and degradation.
Using a biphasic structural coating, including solid structural phase and continuous transport phase, the solid structural phase is composed of materials such as non-fluorinated carbon-based polymers, silicones and fluorinated polymers. The continuous transport phase contains antimicrobial agents such as quaternary ammonium salts and oxidizing molecules, which improve the transmission rate of antimicrobial agents and the durability of the coating by crosslinking molecules.
Elimination of at least 99% by weight, preferably 99.9% by weight of bacteria and viruses within 30 minutes is achieved, improving the durability and water resistance of the coating, ensuring rapid and long-lasting microbial inactivation.
Smart Images

Figure CN116157453B_ABST
Abstract
Description
[0001] Priority data
[0002] This international patent application claims priority to U.S. Provisional Patent Application No. 63 / 037,921, filed on June 11, 2020, and U.S. Patent Application No. 17 / 090,968, filed on November 6, 2020, each of which is hereby incorporated by reference herein. Field of the Invention
[0003] The present invention generally relates to antimicrobial surfaces and coatings, compositions suitable for antimicrobial surfaces and coatings, and methods of making and using the same. Background of the Invention
[0005] Coronavirus disease 2019 (“COVID-19”) is caused by severe acute respiratory syndrome coronavirus 2 (“SARS-CoV-2”). The COVID-19 pandemic has highlighted the importance of environmental cleaning and hygiene management involving various surfaces. Although strict hygiene measures have been implemented, it has proven to be difficult to disinfect surfaces. Even after disinfection, surfaces can become recontaminated.
[0006] Respiratory secretions or droplets expelled by infected individuals can contaminate surfaces and objects, forming fomites (contaminated surfaces). Live SARS-CoV-2 virus can be found on contaminated surfaces for periods ranging from hours to days, depending on the surrounding environment (including temperature and humidity) and the type of surface. See, e.g., Van Doremalen et al., “Aerosol and surface stability of SARS-CoV-2 as compared with SARS-CoV-1,” New England Journal of Medicine 2020;382:1564-1567; Pastorino et al., “Prolonged Infectivity of SARS-CoV-2 in Fomites,” Emerging Infectious Diseases 2020;26(9); and Chin et al., “Stability of SARS-CoV-2 in different environmental conditions,” The Lancet Microbe, e10, April 2, 2020.
[0007] There is consistent evidence that surfaces are contaminated with SARS-CoV-2 and that the virus survives on some surfaces. People who come into contact with potentially infected surfaces are often also in close contact with infected people, making the distinction between respiratory droplet and fomite transmission difficult to discern. However, given the consistent findings of environmental contamination near infected cases and the fact that other coronaviruses and respiratory viruses can be transmitted in this way, fomite transmission is considered a viable mode of transmission for SARS-CoV-2 (World Health Organization, “Transmission of SARS-CoV-2: implications for infection prevention precautions,” July 9, 2020, accessed from www.who.int). Viral transmission can also occur indirectly by touching surfaces in the immediate environment or objects contaminated with virus from an infected person and then touching the mouth, nose, or eyes. While the use of masks in general has become widespread, the use of gloves has not. Even when wearing gloves, the mouth, nose, and eyes are still often touched after touching a contaminated surface.
[0008] Therefore, it is desirable to prevent the spread of pathogens (such as, but not limited to, SARS-CoV-2) through surfaces. One way to reduce the spread of pathogens is to shorten the time humans are susceptible to infection by shortening the survival time of SARS-CoV-2 on solids and surfaces.
[0009] Surfaces can be treated with chemical biocides (such as bleach and quaternary ammonium salts) or UV light to disinfect bacteria and destroy viruses in minutes. Biocides in liquids are able to inactivate at least 99.99% by weight of SARS-CoV-2 in just 2 minutes, attributed to the rapid diffusion of the biocide to the microorganisms and the fact that water helps microbial decomposition. However, these methods cannot always occur in real time after the surface is contaminated.
[0010] Alternatively, an antimicrobial coating can be applied to a surface to kill bacteria and / or eliminate viruses as they are deposited. However, conventional antimicrobial coatings typically require at least 1 hour to reduce bacteria and / or viruses by more than 99.9 wt%, a time scale that is longer than indirect human-to-human interaction, such as in an airplane or shared vehicle. Existing solid coatings are limited by low concentrations of biocides on the surface due to slow biocide transport. The slow diffusion of biocides to the surface through the solid coating competes with the removal of biocides from the surface through human and environmental contact, resulting in limited availability and requiring up to 2 hours to kill 99.9 wt% of bacteria and / or inactivate 99.9 wt% of viruses.
[0011] Water improves transport and aids in microbial decomposition. However, single-material coatings have limited water absorption. Swelling with water is generally an undesirable feature of single-material coatings because it can lead to coating weakening and degradation if it is not designed into the coating.
[0012] In view of the above needs in the art, there is a great need for an antimicrobial coating that enables rapid delivery of biocides to more effectively inactivate SARS-CoV-2 on surfaces. The coating should be safe, convenient to apply or manufacture, and durable. It is particularly desirable that such a coating can eliminate at least 99 wt%, preferably at least 99.9 wt%, and more preferably at least 99.99 wt% of bacteria and / or viruses within 30 minutes of contact, preferably 20 minutes of contact, and more preferably 10 minutes of contact. SUMMARY OF THE INVENTION
[0014] Some variations of the invention provide an antimicrobial structure comprising:
[0015] (a) a solid structural phase comprising a solid structural material;
[0016] (b) a continuous transport phase dispersed in the solid structural phase, wherein the continuous transport phase comprises a solid transport material; and
[0017] (c) an antimicrobial agent contained in said continuous transport phase,
[0018] The solid structural phase and the continuous transport phase are separated by an average phase separation length ranging from about 100 nanometers to about 500 micrometers.
[0019] In some embodiments, the solid structural material is or includes a solid structural polymer selected from the group consisting of: non-fluorinated carbon-based polymers, silicones, fluorinated polymers, and combinations thereof.
[0020] The non-fluorinated carbon-based polymer may be selected from the group consisting of polyalkanes, polyurethanes, polyethers, polyureas, polyesters, and combinations thereof.
[0021] The silicone may be selected from the group consisting of polydimethylsiloxane, polytrifluoropropylmethylsiloxane, polyaminopropylmethylsiloxane, polyaminoethylaminopropylmethylsiloxane, polyaminoethylaminoisobutylmethylsiloxane, and combinations thereof.
[0022] The fluorinated polymer may be selected from the group consisting of fluorinated polyols, perfluorocarbons, perfluoropolyethers, polyfluoroacrylates, polyfluorosilicones, polyvinylidene fluoride, polytrifluoroethylene, and combinations thereof.
[0023] In some embodiments, the solid transport material is or includes a solid transport polymer selected from the group consisting of a hygroscopic polymer, a hydrophobic and non-oleophobic polymer, a hydrophilic polymer, an electrolyte polymer, and combinations thereof.
[0024] The hygroscopic solid transport polymer can be selected from the group consisting of poly(acrylic acid), poly(ethylene glycol), poly(2-hydroxyethyl methacrylate), poly(vinylimidazole), poly(2-methyl-2-oxazoline), poly(2-ethyl-2-oxazoline), poly(vinylpyrrolidone), modified cellulosic polymers, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and combinations thereof.
[0025] The hydrophobic, non-oleophobic solid transfer polymer may be selected from the group consisting of poly(propylene glycol), poly(tetramethylene glycol), polybutadiene, polycarbonate, polycaprolactone, acrylic polyol, and combinations thereof.
[0026] The hydrophilic solid transport polymer may be a polymer having an ionic charge, which may be present in the hydrophilic solid transport polymer, for example, as a carboxylate group, an amine group, a sulfate group, or a phosphate group.
[0027] The electrolyte solid transport polymer may be selected from the group consisting of polyethylene oxide, polypropylene oxide, polycarbonate, polysiloxane, polyvinylidene fluoride, and combinations thereof.
[0028] In a preferred embodiment, the solid structural material is a solid structural polymer, the solid transport material is a solid transport polymer, and the solid structural polymer is cross-linked with the solid transport polymer by a cross-linking molecule. For example, the cross-linking molecule can include at least one moiety selected from the group consisting of an amine moiety, a hydroxyl moiety, an isocyanate moiety, and a combination thereof. In certain embodiments, at least one moiety is an isocyanate moiety, which can be a blocked isocyanate.
[0029] In some embodiments, the continuous transport phase is a solid solution or solid suspension of a solid transport material and an antimicrobial agent.
[0030] In other embodiments, the continuous transport phase contains a transport phase liquid that at least partially dissolves the antimicrobial agent.The transport phase liquid can be selected from the group consisting of water, dialkyl carbonate, propylene carbonate, gamma-butyrolactone, 2-phenoxyethanol, and combinations thereof.
[0031] Alternatively or additionally, the transport phase liquid is selected from polar solvents.
[0032] Alternatively or additionally, the transport phase liquid is selected from ionic liquids.
[0033] In certain embodiments, the transport phase liquid contains one or more water-soluble salts, one or more of which can act as an antimicrobial agent. Exemplary water-soluble salts include, but are not limited to, copper chloride, copper nitrate, zinc chloride, zinc nitrate, silver chloride, silver nitrate, or a combination thereof. In some embodiments, the water-soluble salt is selected from a quaternary ammonium salt, such as benzalkonium chloride, benzethonium chloride, methylbenzethonium chloride, cetylpyridinium chloride, hexadecyltrimethylammonium, cetrimide, tetraethylammonium bromide, didecyldimethylammonium chloride, dioctyldimethylammonium chloride, domiphene, or a combination thereof.
[0034] In certain embodiments, the transport phase liquid is a eutectic liquid salt, optionally derived from an ammonium salt. The eutectic liquid salt may contain an antimicrobial agent or have antimicrobial activity.
[0035] In some embodiments, the continuous transport phase contains a liquid electrolyte, a solid electrolyte, or both a liquid electrolyte and a solid electrolyte.
[0036] In some embodiments, the antimicrobial agent is selected from a quaternary ammonium molecule. Exemplary quaternary ammonium molecules include, but are not limited to, benzalkonium chloride, benzethonium chloride, methylbenzethonium chloride, cetylpyridinium chloride, hexadecyltrimethylammonium, cetrimide, tetraethylammonium bromide, didecyldimethylammonium chloride, dioctyldimethylammonium chloride, and domiphene.
[0037] In some embodiments, the antimicrobial agent is selected from N-halamines. Exemplary N-halamines include, but are not limited to, hydantoin (imidazolidine-2,4-dione); 1,3-dichloro-5,5-dimethylhydantoin; 3-bromo-1-chloro-5,5-dimethylhydantoin; 5,5-dimethylhydantoin; 4,4-dimethyl-2-oxazolidinone; tetramethyl-2-imidazolidinone; and 2,2,5,5-tetramethylimidazolidin-4-one.
[0038] In some embodiments, the antimicrobial agent is selected from oxidizing molecules such as, but not limited to, those selected from the group consisting of sodium hypochlorite, hypochlorous acid, hydrogen peroxide, and combinations thereof.
[0039] In some embodiments, the antimicrobial agent is selected from metal ions, such as, but not limited to, metal ions selected from the group consisting of silver, copper, zinc, and combinations thereof.
[0040] The antimicrobial structure may be characterized in that in the continuous transport phase, the antimicrobial agent has a relative humidity of 10 -16 m 2 / s and 10 -9 m 2 / s diffusion coefficient.
[0041] The antimicrobial structure can be characterized in that the antimicrobial agent is replenished to at least 25% of the initial concentration of the antimicrobial agent on the outer surface of the antimicrobial structure within 100 minutes or less.
[0042] In some embodiments, the antimicrobial structure comprises embedded electrodes configured such that the antimicrobial agent can be electrically or electrochemically recharged.
[0043] The antimicrobial structure may further comprise one or more additives, such as, but not limited to, salts, buffers, UV stabilizers, fillers, or combinations thereof.
[0044] The antimicrobial structure may further comprise one or more protective layers, such as one or more environmental protection layers.
[0045] In some antimicrobial structures, the average phase separation length is from about 0.5 microns to about 100 microns. In certain embodiments, the average phase separation length is from about 1 micron to about 50 microns.
[0046] The antimicrobial structure may be a coating or may be present in a coating. Alternatively or additionally, the antimicrobial structure may be present on the surface of the bulk object. The antimicrobial structure may be the entire bulk object. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is a top view of an antimicrobial structure in some embodiments of the present invention comprising a discrete solid phase that provides wear resistance and a continuous transport phase that transports an antimicrobial agent to an outer surface to inactivate or kill microorganisms.
[0048] Figure 2 is a through-thickness side view of a coating or bulk material that, in some embodiments, comprises a discrete solid phase and a continuous transport phase that stores and transports the antimicrobial agent to an outer layer for inactivating or killing microorganisms.
[0049] Figure 3 is a sketch (through-thickness side view) of an antimicrobial structure having an antimicrobial agent that can be recharged by applying a voltage between two embedded electrodes of opposite polarity in some embodiments of the present invention.
[0050] Figure 4 The impedance magnitude of six poly(ethylene glycol)-polyTHF films having different PEG concentrations after immersion in a 10% benzalkonium chloride solution in Example 3 is shown.
[0051] Figure 5 The graphs showing the specific conductivity and diffusion coefficient of the poly(ethylene glycol)-polyTHF membrane as a function of the PEG concentration after immersion in a 10% benzalkonium chloride solution in Example 3 are shown. DETAILED DESCRIPTION
[0052] The present structures, systems, compositions and methods will now be described in detail with reference to various non-limiting examples.
[0053] This description will enable those skilled in the art to make and use the invention, and describes several embodiments, modifications, variations, alternatives and uses of the invention. These and other embodiments, features and advantages of the invention will become more apparent to those skilled in the art when reference is made to the following detailed description of the invention in conjunction with the accompanying drawings.
[0054] As used in this specification and the appended claims, the singular forms "a / an" and "the" include plural referents unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0055] Unless otherwise indicated, all numerical values expressing conditions, concentrations, dimensions, and the like used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary at least as a function of the particular analytical technique.
[0056] The term "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. "Comprising" is a specialized term used in claim language, meaning that the specified claim elements are essential, but other claim elements may be added and still constitute a concept within the scope of the claim.
[0057] As used herein, the phrase "consisting of excludes any elements, steps, or ingredients not specified in the claim. When the phrase "consisting of" (or variations thereof) appears in a clause in the body of a claim, rather than immediately following the preamble, the phrase is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole. As used herein, the phrase "consisting essentially of limits the scope of a claim to the specified elements or method steps, plus those that do not materially affect the basis and novel feature or features of the claimed subject matter.
[0058] With respect to the terms "comprising," "consisting of," and "consisting essentially of," when one of these three terms is used herein, the presently disclosed and claimed subject matter may include the use of any of the other two terms, except when used with Markush groups. Thus, in some embodiments not otherwise explicitly recited, any instance of "comprising" may be replaced by "consisting of," or alternatively, "consisting essentially of."
[0059] Some variants of the present invention are based on polymer coatings that are solid but have a rapid antimicrobial transmission rate, achieved by a two-phase structure (wherein a solid structure phase is combined with a continuous transmission phase containing an antimicrobial that is phase-separated from the solid structure phase). As defined in this patent application, "antimicrobial" or synonymous "antimicrobial active substances" include bactericides, bactericides, viricides (antivirals), antifungals, antiprotozoa, antiparasitics and biocides. In certain embodiments, antimicrobial agents are specifically bactericides, such as disinfectants, antiseptics and / or antibiotics. In certain embodiments, antimicrobial agents are specifically viricides, or include viricides.
[0060] The present invention solves the technical trade-off between antimicrobial solutions and solid surfaces. Conventional liquid solutions are fast but not persistent. Liquid solutions can reduce the number of bacteria and viruses on a time scale of several minutes, but liquid solutions do not stay on the surface and have a one-time effect. Conventional solid antimicrobial surfaces reduce the number of bacteria and viruses very slowly, causing bacteria and viruses to remain on the surface for a long time. See Behzadinasab et al., "A Surface Coating that Rapidly Inactivates SARS-CoV-2", ACS Appl. Mater. Interfaces 2020, 12, 31, as an example of an antimicrobial coating that takes at least 1 hour to take effect. The slow activity of conventional solid antimicrobial materials is due to the time required for the antimicrobial agent to diffuse to the surface. If these surfaces are dirty, they cannot work because the dirt hinders the transmission of the antimicrobial agent to the surface.
[0061] In contrast, the materials disclosed herein break the trade-off between activity and persistence. The solid structure phase provides persistence on the surface, while the continuous transmission phase allows the antimicrobial agent to move to the microorganism (e.g., virus or bacteria) on the surface at a rate several orders of magnitude faster than the rate that can be achieved by diffusion of a single solid material. The two-phase structure provides durability and rapid transmission to the surface at the same time, wherein the antimicrobial agent can kill or inactivate the microorganism at the surface. The continuous transmission phase can contain an aqueous or non-aqueous solvent or electrolyte to further improve the transmission rate of the antimicrobial agent. In certain embodiments, the continuous transmission phase passively absorbs water from the environment, and the water can improve the transmission rate of the antimicrobial agent and / or improve the effectiveness of the antimicrobial agent.
[0062] Antimicrobial surfaces have many commercial applications in homes (e.g., kitchens and bathrooms), restaurants, clothing and personal protective equipment, automobiles (especially ride-sharing vehicles to inhibit the spread of microorganisms from one person to another), airplanes (e.g., for contaminated surfaces that UV light cannot reach), and inside and outside vehicles used to rescue or move people who have been exposed to diseases and epidemics.
[0063] Some variations of the invention provide an antimicrobial structure comprising:
[0064] (a) a solid structural phase comprising a solid structural material;
[0065] (b) a continuous transport phase dispersed in the solid structural phase, wherein the continuous transport phase comprises a solid transport material; and
[0066] (c) an antimicrobial agent contained in said continuous transport phase,
[0067] The solid structural phase and the continuous transport phase are separated by an average phase separation length ranging from about 100 nanometers to about 500 micrometers.
[0068] Certain variations provide an antimicrobial structure intended to contain an antimicrobial agent, the antimicrobial structure comprising:
[0069] (a) a solid structural phase comprising a solid structural material;
[0070] (b) a continuous transport phase interspersed within the solid structured phase, wherein the continuous transport phase comprises a solid transport material, and wherein the continuous transport phase is capable of comprising an antimicrobial agent (e.g., upon intended use or regeneration),
[0071] The solid structural phase and the continuous transport phase are separated by an average phase separation length ranging from about 100 nanometers to about 500 micrometers.
[0072] In some embodiments, the solid structural material is or includes a solid structural polymer selected from the group consisting of: non-fluorinated carbon-based polymers, silicones, fluorinated polymers, and combinations thereof. These types of polymers are preferred when the solid structural material requires anti-wetting properties (from water or other hydrophilic liquids), providing a dry feeling surface. Hydrophobic and / or lyophobic solid structural materials prevent or minimize dirt adhesion and debris penetration into the entire structure.
[0073] The non-fluorinated carbon-based polymer may be selected from the group consisting of polyalkanes, polyurethanes, polyethers, polyureas, polyesters, and combinations thereof.
[0074] The silicone may be selected from the group consisting of polydimethylsiloxane, polytrifluoropropylmethylsiloxane, polyaminopropylmethylsiloxane, polyaminoethylaminopropylmethylsiloxane, polyaminoethylaminoisobutylmethylsiloxane, and combinations thereof.
[0075] The fluorinated polymer may be selected from the group consisting of fluorinated polyols, perfluorocarbons, perfluoropolyethers, polyfluoroacrylates, polyfluorosilicones, polyvinylidene fluoride, polytrifluoroethylene, and combinations thereof.
[0076] In some embodiments, the solid transport material is or includes a solid transport polymer selected from the group consisting of hygroscopic polymers, hydrophobic and non-oleophobic polymers, hydrophilic polymers, electrolyte polymers, and combinations thereof. As described below, the continuous transport phase may further include a transport phase liquid, which may be organic or inorganic.
[0077] In some embodiments, the solid transport material is or includes a hygroscopic solid transport polymer. For example, the hygroscopic solid transport polymer can be selected from the group consisting of poly(acrylic acid), poly(ethylene glycol), poly(2-hydroxyethyl methacrylate), poly(vinylimidazole), poly(2-methyl-2-oxazoline), poly(2-ethyl-2-oxazoline), poly(vinylpyrrolidone), modified cellulose polymers, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and combinations thereof. For example, the hygroscopic solid transport polymer can be a cross-linked poly(acrylic acid) emulsion polymer (e.g., polymer).
[0078] In some embodiments, the solid transport material is or includes a hydrophobic, non-oleophobic solid transport polymer. For example, the hydrophobic, non-oleophobic solid transport polymer can be selected from the group consisting of poly(propylene glycol) (PPG), poly(tetramethylene glycol) (PTMEG, also known as polytetrahydrofuran or polyTHF), polybutadiene, polycarbonate, polycaprolactone, acrylic polyol, and combinations thereof.
[0079] In some embodiments, the solid transport material is or includes a hydrophilic solid transport polymer. The hydrophilic solid transport polymer can be a polymer generated with an ionic charge, which can be present in the hydrophilic solid transport polymer, for example, as a side chain or main chain carboxylate group, an amine group, a sulfate group, or a phosphate group. In certain embodiments, monomers containing an ionic charge are inserted along the polymer backbone. The hydrophilic solid transport polymer can be combined with an antimicrobial agent.
[0080] In some embodiments, the solid transport material is or includes an electrolyte solid transport polymer. For example, the electrolyte solid transport polymer can be selected from the group consisting of polyethylene oxide, polypropylene oxide, polycarbonate, polysiloxane, polyvinylidene fluoride, and combinations thereof.
[0081] In a preferred embodiment, the solid structural polymer is cross-linked to the solid transport polymer via cross-linking molecules. The cross-linking is preferably covalent, but may also be ionic. When the discrete phase and the continuous phase are covalently cross-linked, a wear-resistant structure is established in the continuous transport phase. In addition, when the structural polymer and the transport polymer are cross-linked, the length scales of the different phases can be controlled, for example to increase the transport rate of the antimicrobial agent.
[0082] For example, the cross-linking molecule (when present) can include at least one moiety selected from the group consisting of an amine moiety, a hydroxyl moiety, an isocyanate moiety, and combinations thereof. Other cross-linking molecules can be used. In certain embodiments, at least one moiety is an isocyanate moiety, which can be a blocked isocyanate.
[0083] In some embodiments, the continuous transport phase is a solid solution or solid suspension of a solid transport material and an antimicrobial agent. For example, when the antimicrobial agent is a liquid, the continuous transport phase can be a solution of the solid transport material and the antimicrobial agent. When the antimicrobial agent is a solid, the continuous transport phase can be a suspension of the solid transport material and the antimicrobial agent.
[0084] In other embodiments, the continuous transport phase contains a transport phase liquid that at least partially dissolves the antimicrobial agent.The transport phase liquid can be selected from the group consisting of water, dialkyl carbonate, propylene carbonate, gamma-butyrolactone, 2-phenoxyethanol, and combinations thereof.
[0085] Alternatively or additionally, the transport phase liquid is selected from a polar solvent. The polar solvent may be a protic polar solvent or an aprotic polar solvent. Exemplary polar solvents include, but are not limited to, water, alcohols, ethers, esters, ketones, aldehydes, carbonates, and combinations thereof. In some embodiments, the transport phase liquid is water passively bound from atmospheric humidity.
[0086] Alternatively or additionally, the transport phase liquid is selected from ionic liquids. Exemplary ionic liquids include, but are not limited to, ammonium-based ionic liquids synthesized from substituted quaternary ammonium salts.
[0087] The transport phase liquid may include a high ion concentration to aid in the transport of the antimicrobial agent and / or enhance the absorption of the fluid, which in turn aids in the transport of the antimicrobial agent.
[0088] In some embodiments, the antimicrobial agent is selected from quaternary ammonium molecules (whether or not classified as ionic liquids). Exemplary quaternary ammonium molecules include, but are not limited to, benzalkonium chloride, benzethonium chloride, methylbenzethonium chloride, cetylpyridinium chloride, hexadecyltrimethylammonium, cetrimide, tetraethylammonium bromide, didecyldimethylammonium chloride, dioctyldimethylammonium chloride, and domiphene. Quaternary ammonium molecules or eutectic mixtures of quaternary ammonium molecules that are liquid at room temperature (ionic liquids or ionic liquid eutectics, respectively) can achieve liquid transmission rates with negligible vapor pressures. Specific examples are tetrabutylammonium heptadecafluorooctanesulfonate (C 24 H 36 F 17 NO3S), whose melting point is <5°C. Another specific example is tetraoctyl ammonium chloride (C 32 H 68 ClN) and tetraheptyl ammonium chloride (C 28 H 60 ClN), which forms a liquid at room temperature (25° C.). The quaternary ammonium molecule may be mixed with an imidazolium-based ionic liquid, a pyridinium-based ionic liquid, a pyrrolidinium-based ionic liquid, and / or a phosphonium-based ionic liquid.
[0089] In certain embodiments, the transport phase liquid contains one or more water-soluble salts, one or more of which can act as an antimicrobial agent. Exemplary water-soluble salts include, but are not limited to, copper chloride, copper nitrate, zinc chloride, zinc nitrate, silver chloride, silver nitrate, or a combination thereof. Other exemplary water-soluble salts include quaternary ammonium salts, such as (but not limited to) the quaternary ammonium molecules described above.
[0090] In certain embodiments, the transport phase liquid is a eutectic liquid salt, optionally derived from an ammonium salt. The eutectic liquid salt may contain an antimicrobial agent or have antimicrobial activity.
[0091] In some embodiments, the antimicrobial agent is selected from N-halamines. N-halamines are compounds that stabilize oxidants (e.g., chlorine contained in the N-halamine molecule) and can be used to kill or inactivate microorganisms. Unlike sodium hypochlorite (bleach), N-halamines remain stable over long periods of time and can be recharged by exposure to oxidants (such as dilute bleach or ozone). Exemplary N-halamines include, but are not limited to, hydantoins (imidazolidine-2,4-dione); 1,3-dichloro-5,5-dimethylhydantoin; 3-bromo-1-chloro-5,5-dimethylhydantoin; 5,5-dimethylhydantoin; 4,4-dimethyl-2-oxazolidinone; tetramethyl-2-imidazolidinone; and 2,2,5,5-tetramethylimidazolidin-4-one. Examples of antimicrobial N-halamines are also disclosed in Lauten et al., Applied and Environmental Microbiology, Vol. 58, No. 4, pp. 1240-1243 (1992), which is incorporated by reference.
[0092] In some embodiments, the antimicrobial agent is selected from oxidizing molecules such as, but not limited to, those selected from the group consisting of sodium hypochlorite, hypochlorous acid, hydrogen peroxide, and combinations thereof.
[0093] In some embodiments, the antimicrobial agent is selected from metal ions, such as, but not limited to, silver, copper, zinc, cobalt, nickel, or a combination thereof. Any metal ion that has at least some antimicrobial activity itself or imparts antimicrobial activity to a compound bound to the metal ion can be used. For example, the metal ion can be present in the form of a metal complex or a metal salt. For example, in certain embodiments, the antimicrobial agent contains a neutral metal (e.g., zero-valent silver, copper, or zinc) that can be dissolved in a liquid and / or can be present as nanoparticles.
[0094] A liquid electrolyte or a solid electrolyte (or both) may be included in the continuous transport phase to increase the rate of transport of the antimicrobial agent.
[0095] An exemplary electrolyte is a complex formed between poly(ethylene oxide) and a metal salt, such as poly(ethylene oxide)-Cu(CF3SO3)2, which is a known copper conductor. Cu(CF3SO3)2 is the copper(II) salt of trifluoromethanesulfonic acid. See Bonino et al., "Electrochemical properties of copper-based polymer electrolytes," Electrochimica Acta, Vol. 37, No. 9, pp. 1711-1713 (1992), which is incorporated by reference.
[0096] When the liquid electrolyte is included in the continuous transport phase, one or more solvents for the liquid electrolyte may be present. For example, the solvent for the liquid electrolyte may be selected from the group consisting of sulfoxide, sulfolane, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, γ-butyrolactone, γ-valerolactone, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, acetonitrile, propionitrile, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, methyl formate, trimethyl phosphate, triethyl phosphate, and mixtures thereof.
[0097] When the liquid electrolyte is included in the continuous transport phase, a salt may be present in the aqueous or non-aqueous solvent. Exemplary salts are transition metals (e.g., V, Ti, Cr, Co, Ni, Cu, Zn, Tb, W, Ag, Cd, or Au), metalloids (e.g., Al, Ga, Ge, As, Se, Sn, Sb, Te, or Bi), alkali metals (e.g., Li, Na, or K), alkaline earth metals (e.g., Mg or Ca), or combinations thereof.
[0098] In some embodiments, the gel electrolyte is contained in the continuous transport phase. The gel electrolyte contains a liquid electrolyte in a polymer host, the liquid electrolyte comprising an aqueous or non-aqueous solvent and a salt. The solvent and the salt may be selected from the above list. The polymer host may be selected from the group consisting of poly(ethylene oxide), poly(vinylidene fluoride), poly(acrylonitrile), poly(methyl methacrylate), poly(vinylidene fluoride-hexafluoropropylene) (PVdF-co-HFP, polycarbonate, polysiloxane, and combinations thereof.
[0099] When a solid electrolyte is included in the continuous transport phase, the solid electrolyte is preferably concentrated enough to achieve sufficient ion penetration. The solid electrolyte can be an oxide, a sulfide, a halide, or a combination thereof. Exemplary solid electrolytes include, but are not limited to, β-alumina, β″-alumina, Cu-β-alumina, Cu-β″-alumina, Ag-β-alumina, and Ag-β″-alumina. β-alumina and β″-alumina are good conductors of mobile ions. β″-alumina is a hard polycrystalline or single crystal ceramic that, when prepared as an electrolyte, complexes with mobile ions such as (but not limited to) Cu 2+ or Ag + β-alumina and / or β″-alumina are also referred to herein as “β-alumina”.
[0100] Other solid electrolytes include yttria-stabilized zirconia, sodium superionic conductors (NASICON), lithium superionic conductors (LISICON), potassium superionic conductors (KSICON), lithium thiogermanate thiophosphate (LGPS), or any combination of the foregoing. Chalcogenide glasses can be used as solid electrolytes. Exemplary chalcogenide glasses include RbI-GeSe2-Ga2Ge3 and CsI-GeSe2-Ga2Ge3.
[0101] The solid electrolyte for conducting copper ions may include cuprous halides, such as (but not limited to) CuCl, CuBr, CuI, or combinations thereof. For some mixed phases, such as RbCuClI, the conductivity at room temperature may reach the order of 0.1 S / cm. The solid electrolyte for conducting copper ions may include copper sulfide Cu x S y , wherein x and y can vary. For example, when y=1, x can be selected from about 1 to less than 2, such as 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or 1.9.
[0102] The solid electrolyte for conducting silver ions may include a silver ion conductor such as, but not limited to, AgI, Ag2SeO4, RbAg4I5, or a combination thereof. AgI has an ionic conductivity of about 0.1 S / cm at 150° C. RbAg4I5 has an ionic conductivity of about 0.1 S / cm at 25° C.
[0103] When a solid electrolyte is present, it can be incorporated into the continuous transport phase as its own continuous or semi-continuous phase, meaning that there is a physical connection between the solid electrolyte regions. However, the solid electrolyte need not be continuous throughout the material. In certain embodiments, the solid electrolyte is incorporated into a solid matrix phase that is different from the continuous transport phase. In these embodiments, the separate solid electrolyte matrix phase can be a polymer, ceramic, metal, or a combination thereof.
[0104] In certain embodiments, the antimicrobial structure further contains one or more layers of antimicrobial storage phases that are different from the continuous transmission phase and the solid structure phase. In these or other certain embodiments, the antimicrobial structure further contains inclusions of antimicrobial storage phases that are different from the continuous transmission phase and the solid structure phase. The antimicrobial storage phase can be made of the same material as the solid transmission material or a different material. For example, both the solid transmission material and the antimicrobial storage phase (when present) can be made of hydrophobic, non-oleophobic polymers. The antimicrobial storage phase can contain an antimicrobial that is initially, continuously, or periodically released into the continuous transmission phase.
[0105] The antimicrobial structure may further comprise one or more additives, such as, but not limited to, salts, buffers, UV stabilizers, fillers, or combinations thereof. Additives, when present, may be incorporated into the solid structural phase, the continuous transport phase, both phases, or neither phase but in a separate phase.
[0106] When the additive is a salt, there will be cations and anions to form a salt. The cation elements may be, for example, Li, Na, K, Mg and / or Ca. The anion elements or groups may be, for example, F, Cl, Br, I, SO3, SO4, NO2, NO3, CH3COO and / or CO3.
[0107] When the additive is a buffer, it may be an inorganic or organic molecule that maintains the pH value or pH range through an acid-base reaction.The buffer may be, for example, discrete or may be bound to a solid transport material.
[0108] When the additive is a UV stabilizer, it can be, for example, an antioxidant (e.g., a thiol), a hindered amine (e.g., a derivative of tetramethylpiperidine), UV absorbing nanoparticles (e.g., CdS, CdTe, or ZnS-Ag nanoparticles), or a combination thereof.
[0109] For example, when the additive is a particulate filler, it can be selected from the group consisting of: silica, alumina, silicates, talc, aluminosilicates, barium sulfate, mica, diatomaceous earth, calcium carbonate, calcium sulfate, carbon, wollastonite, and combinations thereof. For example, the particulate filler is optionally surface-modified with a compound selected from the group consisting of: fatty acids, silanes, alkylsilanes, fluoroalkylsilanes, silicones, alkylphosphonates, alkylphosphonic acids, alkylcarboxylates, alkyldisilazanes, and combinations thereof.
[0110] Figure 1 An exemplary antimicrobial structure 100 is depicted in , which is a top view of the exterior surface of the antimicrobial structure 100. Figure 1 In the embodiment of the present invention, the antimicrobial structure 100 is a dual-phase structure comprising a discrete solid phase 110 that provides wear resistance, and a continuous transmission phase 120 that stores an antimicrobial agent and delivers the antimicrobial agent to an external surface to inactivate or kill microorganisms. An antimicrobial agent (not shown) is preferably selectively contained in the continuous transmission phase 120, so that the antimicrobial structure 100 can destroy microorganisms (e.g., viruses and / or bacteria). Figure 1 The 100 micron scale bar in is exemplary and indicates the length scales of the discrete solid phase 110, the continuous transport phase 120, and the distances between the phases. The structure 100 may be, for example, a coating on a substrate (not shown), or may be a bulk material or object.
[0111] Figure 2An exemplary antimicrobial structure 200 is depicted in FIG, which is a full thickness side view of a coating or bulk material. There is an outer layer 250, which may contain microorganisms from environmental sources (microorganisms not shown) and is generally exposed to the environment. Figure 2 In the embodiment of the present invention, the antimicrobial structure 200 is a biphasic structure containing a discrete solid phase 210 and a continuous transmission phase 220, which stores and transmits the antimicrobial agent to the outer layer 250 to inactivate or kill microorganisms that may be present there. The antimicrobial agent (not shown) is preferably selectively included in the continuous transmission phase 220, so that the antimicrobial structure 200 can destroy microorganisms (e.g., viruses and / or bacteria) after the antimicrobial agent is transmitted to the outer layer 250 and / or potentially after the microorganism diffuses from the outer layer 250 into the continuous transmission phase 220 (which exposes the microorganism to the antimicrobial agent). The structure 200 can be, for example, a coating (not shown) on a substrate, or can be a bulk material or object. The substrate (if present) will typically be opposite the distal side of the outer layer 250.
[0112] In some embodiments, the antimicrobial structure comprises embedded electrodes configured such that the antimicrobial agent is electrically or electrochemically rechargeable.As used herein, "rechargeable" means rechargeable during use as well as initially rechargeable when first deployed.
[0113] Figure 3 is a sketch (through-thickness side view of the coating or material) of an antimicrobial structure 305 with a rechargeable antimicrobial agent. Figure 3 In the embodiment, the antimicrobial structure 305 includes antimicrobial materials 300a / 300b / 300c, which are composed of Figure 2 , i.e., the material 300a / 300b / 300c includes a solid structural phase ( Figure 2 210) and continuous transmission phase ( Figure 2 220), for the purpose of clarity, Figure 3 The materials 300a / 300b / 300c are shown in uniform grayscale.
[0114] exist Figure 3In the embodiment of the present invention, there are two embedded electrodes 330 and 340 in the antimicrobial structure 305, wherein electrode 330 is depicted as a positive electrode layer and electrode 340 is depicted as a negative electrode layer. The electrode polarity can be switched. The electrodes can be made of, for example, a metal grid, a mesh, or a perforated plate, and can contain metals and catalysts, such as Ti, Pt, Ru, Ir, or a combination thereof. Electrode leads (not shown) will carry current to or from the electrodes. Although electrodes 330, 340 are depicted as embedded layers, other electrode configurations are possible, including, for example, one or two electrodes as outer layers, one of which is integrated with the wall of the base substrate or object, or non-planar electrode structures.
[0115] exist Figure 3 In the embodiment of the present invention, there is an outer layer 350, which may contain microorganisms from environmental sources (microorganisms not shown) and is generally exposed to the environment. Structure 305 can be, for example, a coating on a substrate (not shown), or can be a bulk material or object. The substrate (if present) will typically be opposite to the outer layer 350 distally.
[0116] Suitable antimicrobial agents can be electrochemically charged or recharged (e.g., after a period of use). In a rechargeable configuration, the continuous transport phase will typically be wetted by a liquid solution containing water or another solvent and / or a liquid electrolyte (optionally, a gel electrolyte). The liquid solution contains the antimicrobial agent or a precursor of the antimicrobial agent. The liquid solution may also contain salts and / or pH buffers.
[0117] For example, when the selected antimicrobial agent is sodium hypochlorite (NaClO) and / or hypochlorous acid (HOCl), sodium chloride (NaCl) can be used as an antimicrobial precursor. In particular, for example, a voltage can be applied so that the NaCl dissolved in the transport phase in material 300b (between electrodes 330, 340) is electrochemically converted into sodium hypochlorite and / or hypochlorous acid according to pH. NaClO and / or HOCl have antimicrobial activity. After electrochemically generating NaClO and / or HOCl, NaClO and / or HOCl penetrate (through the continuous transport phase) into the entire structure 305, i.e., from material 300b into materials 300a and 300c. The desired position is material 300a, especially near or at the outer layer 350, where microorganisms may be concentrated. Since the NaClO and / or HOCl present in material 300c are typically not removed by environmental forces during use, there is usually a concentration gradient in the direction toward the outer layer 350, which is required for effective replenishment and thus recharging. Periodic washing or soaking with saline solutions (eg, 2500-6000 ppm NaCl) and buffers may be used to maintain pH. Periodic soaking with liquid electrolytes may be used to increase the rate of delivery of the antimicrobial agent or its precursor.
[0118] As another example, sodium hypochlorite and / or hypochlorous acid may be generated by applying a voltage between electrodes 330, 340, as described above, where NaClO and / or HOCl are one or more antimicrobial precursors used to recharge the N-halamine that forms the selected antimicrobial agent.
[0119] The antimicrobial structure may further comprise one or more protective layers, such as one or more environmental protection layers. Thus, the antimicrobial structure may be a multilayer structure, which may contain two, three, four or more layers. In some embodiments, an outer layer is present to seal the active component from the environment while retaining and diffusing the antimicrobial agent over time.
[0120] There may be one or more cover layers that protect the liquid-like layer below the cover layer, reducing evaporation of the liquid. In these embodiments, microorganisms (e.g., bacteria or viruses) may enter through the cover layer to reach the antimicrobial agent below the cover layer. Alternatively or additionally, the microorganism may remain on the cover layer, and the antimicrobial agent diffuses through the cover layer to reach the microorganism.
[0121] In certain embodiments, the antimicrobial structure comprises a porous top layer and an absorbent inner layer comprising an antimicrobial agent. In these embodiments, the porous top layer may comprise, for example, expanded polytetrafluoroethylene (e.g., ) material that allows vapor but not liquid exchange. A bottom sealing layer may be incorporated to prevent loss of antimicrobial agent.
[0122] In certain embodiments, the antimicrobial structure comprises a multi-layer substructure wherein at least one layer comprises a dual phase structure as disclosed herein, and wherein an interior or encapsulating layer comprises an antimicrobial agent and / or preferentially captures microorganisms to enhance antimicrobial efficacy.
[0123] The antimicrobial structure may be characterized in that in the continuous transport phase, the antimicrobial agent has a relative humidity of 10 -16 m 2 / s and 10 -9 m 2 In various embodiments, the antimicrobial agent diffusion coefficient is about or at least about 10 -16 m 2 / s, preferably 10 -14 m 2 / s, more preferably 10 -12 m 2 / s, even more preferably 10 -10 m 2 / s, or most preferably 10 -9 m 2 / s, measured at 25°C and 1 bar. Order of magnitude 10 -9 m 2 The diffusion coefficient of / s is liquid-like and is usually much higher than that of a pure solid.
[0124] The antimicrobial structures disclosed herein are not limited to transporting antimicrobial agents only by pure diffusion. Depending on the specific selection of materials, antimicrobial agents, and the method of using the structure, the actual transport can occur through various mass transfer mechanisms, including but not limited to Fickian diffusion, non-Fickian diffusion permeation, adsorption transport, dissolution-diffusion, charge-driven flow, convection, capillary-driven flow, etc. As just one example, when the antimicrobial structure is used in an automobile, the structure can be moved quickly in space, so that the antimicrobial agent experiences a certain amount of centrifugal convection.
[0125] Even when mass transfer is dominated by diffusion, the actual rate of transfer (flux) of the antimicrobial agent through the structure depends not only on the diffusion coefficient, but also on the three-dimensional concentration gradient, temperature, and possible other factors (such as pH). In various embodiments, the actual flux of the antimicrobial agent through the structure is about or at least about 2×, 3×, 4×, 5×, 10×, 20×, 30×, 40×, 50×, 100×, 200×, 300×, 400×, 500×, or 1000× higher than the flux through the solid material. One of ordinary skill in the art can calculate or estimate the transmission flux for a given structural geometry and material, or perform experiments to determine such flux.
[0126] The feature of antimicrobial structure will be the initial concentration of antimicrobial (before being exposed to microorganism).The initial concentration of antimicrobial can be selected based on the type of antimicrobial and the intended use of antimicrobial structure and / or other factors.In different embodiments, the initial concentration of antimicrobial is about, at least about or at most about 0.00001wt%, 0.0001wt%, 0.001wt%, 0.01wt%, 0.1wt%, 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt% or 50wt% based on the mass of antimicrobial divided by the gross mass of all components in 0.1%, 1%, 5% or 10% depth from the surface to the body structure.
[0127] The feature of antimicrobial structure can be that in 100 minutes or shorter time, antimicrobial agent is supplemented to at least 25% of the initial concentration of antimicrobial agent on the outer surface of antimicrobial structure. In different embodiments, in 100 minutes or shorter time, antimicrobial agent is supplemented to at least 30%, 40%, 50%, 60%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, 99.9% or 100% of the initial concentration of antimicrobial agent on the outer surface of antimicrobial structure. In these or other embodiments, in 90,80,70,60,50,40,30,20,15,10,5,4,3,2 or 1 minute or shorter time, antimicrobial agent is supplemented to at least 25% of the initial concentration of antimicrobial agent on the outer surface of antimicrobial structure. Preferably, the antimicrobial agent is replenished to at least 50% of the initial concentration of the antimicrobial agent on the outer surface of the antimicrobial structure within 60, 30, 20, 15, 10, 5, 4, 3, 2, or 1 minute or less. These ranges can be achieved in embodiments without or with an electrically or electrochemically rechargeable antimicrobial agent.
[0128] In some antimicrobial structures, the average phase separation length is from about 0.5 micron to about 100 microns. In certain embodiments, the average phase separation length is from about 1 micron to about 50 microns. In various embodiments, the average phase separation length is from 100 nanometers to 100 microns, 100 nanometers to 500 microns, 100 nanometers to 100 microns, 100 nanometers to 200 microns, 100 nanometers to 200 microns, at least 200 nanometers, at least 500 nanometers, at least 1 micron, at least 5 microns, at most 10 microns, at most 50 microns, at most 100 microns, or at most 500 microns. Exemplary average phase separation lengths are about, at least about, or at most about 0.1, 0.2, 0.3, 0.4, 0.5, 1, 2, 3, 4, 5, 10, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, or 500 microns, including all intermediate ranges.
[0129] The antimicrobial structure may be a coating or may be present in a coating. Alternatively or additionally, the antimicrobial structure may be present on the surface of a bulk object. The antimicrobial structure may be the entire bulk object, without an underlying substrate or other solid structure.
[0130] Various options can be incorporated into the antimicrobial structure or the method using the antimicrobial structure to improve the overall efficacy. For example, the antimicrobial structure can include physical features (e.g., nanorods or nanopores) with similar length scales (e.g., about 50-150 nanometers) as the virus, so that such physical features enhance the capture of the virus on the surface. The physical features can be made of, for example, bound quaternary ammonium compounds (see, for example, US 2019 / 0106525, which is incorporated by reference), alkyl chains, or curable polycations (e.g., polyethyleneimine).
[0131] The ionic layer can be combined with the triggered exothermic component to add heat to the antimicrobial structure. For example, CaCl2 can be incorporated into the antimicrobial structure as a solid additive to react with water (e.g., aerosol derived from an infected person). The heat generated increases the transmission rate of the antimicrobial agent. For example, see Chin et al., "Stability of SARS-CoV-2 in different environmental conditions", The Lancet Microbe, e10, April 2, 2020 (including supplementary content), which is incorporated by reference.
[0132] The continuous transport phase can be configured to dissolve viruses and / or bacteria to help break their outer surface. For example, detergent molecules can be included in the continuous transport phase. In certain embodiments, alkyl chains or amphipathic compounds that are bound are added to the continuous transport phase. The functions of the alkyl chains or amphipathic compounds that are bound are similar to detergent molecules and will help destroy bacteria or viral membranes. In these or other embodiments, a surfactant can be included in the continuous transport phase. The surfactant can be an anionic, cationic, zwitterionic or nonionic surfactant.
[0133] The solid structural phase can be made of or include an antifouling polymer to minimize the presence of dirt and debris (eg, oil) and make the surface easier to clean. Exemplary antifouling polymers are segmented copolymers, discussed further below.
[0134] In some embodiments, the antimicrobial agent is incorporated into the continuous transport phase during the synthesis of the antimicrobial structure. For example, in certain embodiments, the antimicrobial agent is incorporated into the continuous transport phase after the antimicrobial structure is synthesized, such as by infiltrating a liquid containing the antimicrobial agent into the continuous transport phase, or by electrochemically generating the antimicrobial agent in situ using a voltage applied between electrodes.
[0135] Some embodiments will now be further described with reference to the synthesis of the solid structural phase and the continuous transport phase, the preferred dual phase structures, and the selective incorporation of the antimicrobial agent in the continuous transport phase.
[0136] Some embodiments are premised on preferential incorporation of the antimicrobial agent in one phase of the multiphase polymer coating.The structure of the microphase separated polymer network provides a reservoir for the antimicrobial agent in the continuous phase.
[0137] As contemplated herein, "microphase separated" means that the first and second solid materials (eg, soft segments) are physically separated at a microphase separation length scale of from about 0.1 microns to about 500 microns.
[0138] Unless otherwise indicated, all references to "phase" in this patent application are related to solid phase or fluid phase. "Phase" is a spatial region (forming a thermodynamic system) throughout which all physical properties of the material are substantially uniform. Examples of physical properties include density and chemical composition. A solid phase is a solid material region that is chemically uniform and physically different from other regions of a solid material (or any liquid or vapor material that may be present). A solid phase is typically polymeric and may melt or at least undergo a glass transition at elevated temperatures. Mentioning multiple solid phases in a composition or microstructure means that there are at least two different solid material phases without forming a solid solution or a homogeneous mixture.
[0139] In some embodiments, the antimicrobial agent is in the form of a fluid. Preferably, the fluid is not completely in the vapor phase at 25°C because the vapor is prone to leaking from the structure. However, at 25°C, the fluid can contain vapor in equilibrium with the liquid. In addition, in certain embodiments, the fluid is in liquid form at 25°C, but at least partially in vapor form at a higher use temperature (such as 30°C, 40°C, 50°C, or higher).
[0140] "Disposing" a liquid in a solid material means incorporating the liquid into the bulk phase of the solid material, and / or onto the surface of particles of the solid material. The liquid will be in close physical proximity to the solid material, either intimately and / or adjacently. Disposing means various mechanisms including chemical or physical binding, including but not limited to chemical or physical absorption, chemical or physical adsorption, chemical bonding, ion exchange, or reactive inclusions (which may convert at least some of the liquid into another component or different phase that may contain the solid). In addition, the liquid disposed in the solid material may or may not be in thermodynamic equilibrium with the local composition or environment. The liquid may or may not be permanently contained in the structure; for example, depending on volatility or other factors, some of the liquid may be lost to the environment over time.
[0141] "Selectively" disposed in the continuous transport phase, or "selective" to the continuous transport phase, means that of the antimicrobial agent disposed throughout the structure, at least 51%, preferably at least 75%, and more preferably at least 90% of the antimicrobial agent is disposed only in the continuous transport phase. In various embodiments, the selectivity to the continuous transport phase is about or at least about 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, or 100%.
[0142] In some embodiments, the liquid is added to the polymer, such as by immersion and soaking into the polymer. In these embodiments, the liquid can be absorbed into the solid polymer. In certain embodiments, the liquid absorption causes the polymer to swell, which means that the volume of the polymer increases due to the absorption of the liquid. The liquid can, but need not, be classified as a solvent for the solid polymer that causes it to swell.
[0143] The phase separated microstructure preferably comprises discrete islands of one material (solid structural phase) in a continuous sea of another material (continuous transport phase).The continuous phase provides complete pathways in the material for transporting mass and / or charge.
[0144] In some embodiments, there are both phase separated inclusions of the same chemical material, as well as physically and chemically different materials as additional inclusions.
[0145] The solid structure phase and the continuous transmission phase can exist as phase separation regions of copolymers (such as block copolymers). As expected herein, "block copolymers" means copolymers containing linear arrangements of blocks, wherein each block is defined as a part of a polymer molecule, wherein these monomer units have at least one formation or structural feature not present in adjacent parts. It is preferred to provide segmented block copolymers of two (or more) phases. An exemplary segmented copolymer is a urethane-urea copolymer. In certain embodiments, segmented polyurethanes include microphase separation structures of fluorinated and non-fluorinated species.
[0146] In some embodiments, segmented copolymers are used where the first soft segment forms a continuous matrix and the second soft segment is a plurality of discrete inclusions. In other embodiments, the first soft segment is a plurality of discrete inclusions and the second soft segment forms a continuous matrix.
[0147] Segmented copolymers are typically produced by combining soft segments of flexible oligomers terminated with alcohol or amine reactive groups with multifunctional isocyanates. When the isocyanate is provided in excess relative to the alcohol / amine reactive groups, a viscous prepolymer mixture with a known distribution of chain lengths is formed. This is then cured into a high molecular weight network by the addition of amine or alcohol reactive groups to a ratio of isocyanate to amine / alcohol groups of one. The product of this reaction is a backbone having alternating segments: soft segments of flexible oligomers and hard segments of the reaction product of low molecular weight isocyanates with alcohols / amines.
[0148] Due to the chemical immiscibility of the two phases, the material typically phase separates on the length scale of these individual molecular blocks, resulting in a microstructure of flexible regions adjacent to rigid segments strongly associated through hydrogen bonding of the urethane / urea moieties. This combination of flexible and associative components typically results in a physically cross-linked elastomeric material.
[0149] Some variations of the invention utilize segmented copolymer compositions comprising:
[0150] (a) one or more first soft segments selected from fluoropolymers having an average molecular weight of from about 500 g / mol to about 20,000 g / mol, wherein the fluoropolymer is (α,ω)-hydroxyl terminated, (α,ω)-amine terminated and / or (α,ω)-thiol terminated;
[0151] (b) one or more second soft segments selected from polyesters or polyethers, wherein the polyesters or polyethers are (α,ω)-hydroxyl terminated, (α,ω)-amine terminated and / or (α,ω)-thiol terminated;
[0152] (c) one or more isocyanate species having an isocyanate functionality of 2 or greater, or a reactive form thereof;
[0153] (d) one or more polyol or polyamine chain extenders or crosslinkers, or reactive forms thereof,
[0154] wherein the first soft segment and the second soft segment may (in some embodiments) be microphase separated at a microphase separation length scale of from about 0.1 micrometer to about 500 micrometers, and
[0155] Optionally, the molar ratio of the second soft segment to the first soft segment is less than 2.0.
[0156] In some embodiments, the fluoropolymer exists in a triblock structure:
[0157]
[0158] in:
[0159] X, Y = CH2-(O-CH2-CH2)p -T, and X and Y are independently selected;
[0160] p = 1 to 50;
[0161] T is a hydroxyl, amine, or thiol terminal group;
[0162] m=0 to 100 (in some embodiments, m=1 to 100); and
[0163] n=0 to 100 (in some embodiments, n=1 to 100).
[0164] In some embodiments, the continuous transport phase includes a polyelectrolyte and a counter ion of the polyelectrolyte. For example, the polyelectrolyte can be selected from the group consisting of: poly(acrylic acid) or a copolymer thereof, a cellulose-based polymer, carboxymethyl cellulose, chitosan, poly(styrene sulfonate) or a copolymer thereof, poly(acrylic acid) or a copolymer thereof, poly(methacrylic acid) or a copolymer thereof, poly(allylamine), and combinations thereof. For example, the counter ion can be selected from the group consisting of: H + , Li + 、Na + , K + 、Ag + , Ca 2+ Mg 2+ ,La 3+ , C 16 N + 、F - , Cl - Br - ,I - 、BF4 - 、SO4 2- PO4 2- , C 12 SO3 - , and combinations thereof.
[0165] Other ionic species in combination with counterions may also be used in the continuous transport phase. Generally, in some embodiments, the ionic species may be selected from the group consisting of: ionizable salts, ionizable molecules, zwitterionic components, polyelectrolytes, ionomers, and combinations thereof.
[0166] An "ionomer" is a polymer composed of ionomer molecules. An "ionomer molecule" is a macromolecule in which a substantial (e.g., greater than 1 mol%, 2 mol%, 5 mol%, 10 mol%, 15 mol%, 20 mol%, or 25 mol%) proportion of the constituent units has ionizable groups or ionic groups, or both.
[0167] Depending on the level of substitution of ionic groups and how the ionic groups are incorporated into the polymer structure, polymers are classified as ionomers and polyelectrolytes. For example, polyelectrolytes also have ionic groups covalently bonded to the polymer backbone, but have a higher molar substitution level of ionic groups (such as greater than 50 mol%, typically greater than 80 mol%). Polyelectrolytes are polymers whose repeating units carry electrolyte groups. Polyelectrolyte properties are therefore similar to both electrolytes (salts) and polymers. Like salts, their solutions are conductive. Like polymers, their solutions are usually viscous.
[0168] In some embodiments, the continuous transport phase comprises a polymer, such as a polyurethane, polyurea, polysiloxane, or a combination thereof, having at least some charge along the polymer backbone. The polymer charge can be achieved by incorporating ionic monomers (such as dimethylol propionic acid) or other ionic species. The degree of charge of the polymer can vary, for example, about or at least about 1, 2, 5, 10, 15, 20, or 25 mol% of the polymer repeating units are ionic repeating units.
[0169] In some embodiments, the continuous transport phase comprises an ionic species selected from the group consisting of: (2,2-bis-(1-(1-methylimidazolium)-methylpropane-1,3-diol bromide), 1,2-bis(2′-hydroxyethyl)imidazolium bromide, (3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)-3-methyl-1H-3λ 4 -imidazol-1-ium bromide, 2,2-bis(hydroxymethyl)butyric acid, N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid, N-methyl-2,2'-iminodiethanol, 3-dimethylamino-1,2-propanediol, 2,2-bis(hydroxymethyl)propionic acid, 1,4-bis(2-hydroxyethyl)piperazine, 2,6-diaminohexanoic acid, N,N-bis(2-hydroxyethyl)glycine, 2-hydroxypropionic acid hemi-calcium salt, dihydroxymethylpropionic acid, N-methyldiethanolamine, N-ethyldiethanolamine, N-propyldiethanolamine, N-benzyldiethanolamine, N-tert-butyldiethanolamine, bis(2-hydroxyethyl)benzylamine, bis(2-hydroxypropyl)aniline, and homologues, combinations, derivatives, or reaction products thereof.
[0170] The liquid may be introduced into the continuous transport phase actively, passively, or a combination thereof. In some embodiments, the liquid is actively introduced into the continuous transport phase by spraying the liquid, depositing from a vapor phase derived from the liquid, liquid injection, bath immersion, or other techniques. In some embodiments, the liquid is passively introduced into the continuous transport phase by allowing the liquid to be naturally extracted from the standard atmosphere, or from a local atmosphere that has been adjusted to contain one or more desired liquids in the form of vapor or droplets (e.g., mist).
[0171] In certain embodiments, the desired additive is generally solid at room temperature and is first dissolved or suspended in a liquid which is then disposed in the continuous transport phase.
[0172] In certain other embodiments, the desired additive is generally solid at room temperature and is first melted to produce a liquid, which is then disposed in the continuous transport phase. For example, in the continuous transport phase, the desired additive may partially or completely solidify back into a solid, or may form a multiphase material.
[0173] Some potential additives contain reactive groups that react inadvertently with chemical groups contained in the polymer precursor. Therefore, in some cases, there is incompatibility with liquid species in the resin during chemical synthesis and polymerization. Adding reactive fluid additives to the reaction mixture during the synthesis process can significantly change the stoichiometry and backbone structure, while changing physical and mechanical properties. A strategy to avoid this problem is to block the reactive groups (e.g., alcohols, amines, and / or thiols) in the fluid additive with chemical protecting groups, making it inert to other reactive chemical groups (e.g., isocyanates) in the coating precursor.
[0174] In particular, a reactive position can be temporarily blocked by converting it into a new functional group that does not interfere with the desired transformation. This blocking group is often referred to as a "protecting group." Incorporating a protecting group into a synthesis requires at least two chemical reactions. The first reaction converts the interfering functional group into a different functional group that does not compete with the desired reaction (or competes at a lower reaction rate). This step is called protection. The second chemical step converts the protecting group back to the original group in a subsequent synthesis stage. This latter step is called deprotection.
[0175] In some embodiments where the additive contains an alcohol, amine, and / or thiol group, the additive thus contains a chemical protecting group to prevent or inhibit the reaction of the alcohol, amine, and / or thiol group with the isocyanate. For example, the protecting group can be designed to deprotect upon reaction with atmospheric moisture.
[0176] In the case of an additive containing an alcohol group, the protecting group can be selected from the alcohol protecting group of silyl ethers. For example, the protecting group can be selected from the group consisting of trimethyl silyl ether, isopropyl dimethyl silyl ether, tert-butyl dimethyl silyl ether, tert-butyl diphenyl silyl ether, tribenzyl silyl ether, triisopropyl silyl ether, and combinations thereof. In these or other embodiments, the protecting group for protecting alcohol can be selected from the group consisting of 2,2,2-trichloroethyl carbonate, 2-methoxyethoxymethyl ether, 2-naphthyl methyl ether, 4-methoxybenzyl ether, acetate, benzoate, benzyl ether, benzyloxymethyl acetal, ethoxyethyl acetal, methoxymethyl acetal, methoxypropyl acetal, methyl ether, tetrahydropyranyl acetal, triethyl silyl ether, and combinations thereof.
[0177] In the case of an additive containing an amine group, the protecting group may be selected from the amine protecting groups of carbamates, such as (but not limited to) vinyl carbamate. Alternatively or additionally, the protecting group may be selected from the amine protecting groups of ketamines. In these or other embodiments, the protecting group for protecting the amine may be selected from the group consisting of 1-chloroethylcarbamate, 4-methoxybenzenesulfonamide, acetamide, benzylamine, benzyloxycarbamate, formamide, methylcarbamate, trifluoroacetamide, tert-butoxycarbamate, and combinations thereof.
[0178] In the case of additives containing thiol groups, the protecting group may be selected from, for example, S-2,4-dinitrophenyl sulfide and / or S-2-nitro-1-phenylethyl sulfide.
[0179] When water is the deprotecting agent, the typical reaction mechanism is simple hydrolysis. Water is generally nucleophilic enough to break off the leaving group and deprotect the species. An example of this is the protection of an amine with a ketone to form ketamine. When the amines alone react too quickly to be practically mixed, they can be mixed with isocyanates. In practice, the ketamine reagent is inert, but after mixing and casting into a film, atmospheric moisture will diffuse into the coating, removing the ketone (which itself will evaporate) and leaving the amine behind to react rapidly in situ with the nearby isocyanate.
[0180] Many deprotecting agents require high pH, low pH, or redox chemistry to work. However, some protecting groups are unstable enough that water alone is sufficient to cause deprotection. If possible, the preferred strategy to spontaneously deprotect the molecule is by reaction with atmospheric moisture, such as an atmosphere containing from about 10% to about 90% relative humidity at ambient temperature and pressure. A well-known example is the room temperature vulcanization of silicones. The silyl ethers in these systems are deprotected by moisture, thereby reacting the free Si-OH with other silyl ethers to form Si-O-Si covalent bonds, thereby forming a network.
[0181] In other embodiments, the chemical deprotection step is actively performed, for example by introducing a deprotecting agent and / or adjusting mixture conditions, such as temperature, pressure, pH, solvent, electromagnetic field or other parameters.
[0182] This specification hereby incorporates by reference Greene and Wuts, Protective Groups in Organic Synthesis, 4th edition, John Wiley & Sons, New York, 2007, for its teachings on the role of protecting groups, synthesis of protecting groups, and deprotection protocols, including adjustment of pH, for example by addition of acid or base, to cause deprotection.
[0183] As contemplated in this patent application, "hygroscopic" means that the material is able to attract and retain water molecules from the surrounding environment. Water uptake of various polymers is described in Thijs et al., "Water uptake of hydrophilic polymers determined by a thermal gravimetric analyzer with a controlled humidity chamber," J. Mater. Chem. (17) 2007, 4864-4871, which is hereby incorporated by reference herein. In some embodiments, the hygroscopic material is characterized by a water absorption capacity of at least 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 wt % H2O absorption at 90% relative humidity and 30°C.
[0184] In some embodiments using segmented copolymers, one of the first soft segment and the second soft segment is oleophobic. Oleophobic materials have a weak affinity for oil. As contemplated herein, the term "oleophobic" means a material having a hexadecane contact angle greater than 90°. Oleophobic materials may also be classified as lipophobic.
[0185] In some embodiments using segmented copolymers, one of the first soft segment and the second soft segment can be a "low surface energy polymer", which means a polymer having a surface energy of no greater than 50 mJ / m 2 In some embodiments, one of the first soft segment and the second soft segment has a surface energy of from about 5 mJ / m 2 About 50mJ / m 2 surface energy.
[0186] In some embodiments using segmented copolymers, the first soft segment or the second soft segment can be or include a fluoropolymer, such as, but not limited to, a fluoropolymer selected from the group consisting of polyfluoroethers, perfluoropolyethers, fluoroacrylates, fluorosilicones, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), copolymers of ethylene and trifluoroethylene, copolymers of ethylene and chlorotrifluoroethylene, and combinations thereof.
[0187] In these or other embodiments, the first soft segment or the second soft segment can be or include a siloxane. Siloxane contains at least one Si-O-Si bond. Siloxane can be composed of polymerized siloxane or polysiloxane (also known as silicone). An example is polydimethylsiloxane.
[0188] In some embodiments, the molar ratio of the second soft segment to the first soft segment is about 2.0 or less. In various embodiments, the molar ratio of the second soft segment to the first soft segment is about 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 1.95.
[0189] It should be noted that (α,ω)-terminated polymers are terminated at each end of the polymer. The α-terminus may be the same or different from the ω-terminus at the opposite end. The fluoropolymers and / or polyesters or polyethers may be terminated with a combination of hydroxyl groups, amine groups, and thiol groups, in addition to other possible end-capping groups. It should be noted that thiols may react with -NCO groups (usually catalyzed by tertiary amines) to form thiocarbamates.
[0190] It should also be noted that in the present disclosure, "(α,ω)-capping" includes branching at the terminal end, so that the number of caps per polymer molecule can be greater than 2. The polymers herein can be linear or branched, and in addition to the terminal (α,ω) capping, various capping and functional groups can be present within the polymer chain.
[0191] In this specification, "polyurethane" is a polymer comprising a chain of organic units joined by urethane linkages, where "urethane" refers to N(H)-(C=O)-O-. Polyurethanes are generally produced by reacting an isocyanate containing two or more isocyanate groups per molecule with one or more polyols containing an average of two or more hydroxyl groups per molecule in the presence of a catalyst.
[0192] Polyols are polymers with an average of two or more hydroxyl groups per molecule. For example, α,ω-hydroxy-terminated perfluoropolyethers are a class of polyols.
[0193] "Isocyanate" is a functional group having the formula -N=C=O. For the purposes of this disclosure, OC(=O)-N(H)-R is considered a derivative of isocyanate. "Isocyanate functionality" refers to the number of isocyanate reactive sites on a molecule. For example, a diisocyanate has two isocyanate reactive sites, and thus has an isocyanate functionality of 2. A triisocyanate has three isocyanate reactive sites, and thus has an isocyanate functionality of 3.
[0194] "Polyfluoroether" refers to a class of polymers containing ether groups (an oxygen atom linked to two alkyl or aryl groups) in which at least one hydrogen atom in the alkyl or aryl groups is replaced by a fluorine atom.
[0195] "Perfluoropolyethers" (PFPEs) are a highly fluorinated subset of polyfluoroethers in which all hydrogen atoms in the alkyl or aryl groups are replaced by fluorine atoms.
[0196] "Polyurea" is a polymer comprising a chain of organic units joined by urea linkages, where "urea" refers to N(H)-(C=O)-N(H)-. Polyureas are typically produced by reacting an isocyanate containing two or more isocyanate groups per molecule with one or more polyfunctional amines (e.g., diamines) containing an average of two or more amine groups per molecule, optionally in the presence of a catalyst.
[0197] A "chain extender or cross-linking agent" is a compound (or mixture of compounds) that links long molecules together and thereby completes the polymer reaction. Chain extenders or cross-linking agents are also referred to as curing agents, curatives, or hardeners. In polyurethane / urea systems, a curing agent typically consists of hydroxyl-terminated or amine-terminated compounds that react with isocyanate groups present in the mixture. Diols form urethane linkages as curing agents, while diamines form urea linkages as curing agents. The choice of chain extenders or cross-linking agents can be determined by the end groups present on a given prepolymer. In the case of isocyanate end groups, curing can be accomplished, for example, by chain extension using multifunctional amines or alcohols. Chain extenders or cross-linking agents can have an average functionality greater than 2 (e.g., 2.5, 3.0, or greater) (i.e., more than diols or diamines).
[0198] In some embodiments, the polyester or polyether is selected from the group consisting of poly(formaldehyde), poly(ethylene glycol), poly(propylene glycol), poly(tetrahydrofuran), poly(glycolic acid), poly(caprolactone), poly(ethylene adipate), poly(hydroxybutyrate), poly(hydroxyalkanoate), and combinations thereof.
[0199] In some embodiments, the isocyanate species is selected from the group consisting of 4,4′-methylenebis(cyclohexyl isocyanate), hexamethylene diisocyanate, cycloalkyl-based diisocyanates, toluene-2,4-diisocyanate, 4,4′-methylenebis(phenyl isocyanate), isophorone diisocyanate, and combinations or derivatives thereof.
[0200] In some embodiments, the polyol or polyamine chain extender or crosslinker has a functionality of 2 or greater. At least one polyol or polyamine chain extender or crosslinker can be selected from the group consisting of 1,4-butanediol, 1,3-propylene glycol, 1,2-ethylene glycol, glycerol, trimethylolpropane, ethylenediamine, isophoronediamine, diaminocyclohexane, and homologs, derivatives, or combinations thereof. In some embodiments, a polymeric form of a polyol chain extender or crosslinker is utilized, typically with a hydrocarbon or acrylic backbone having hydroxyl groups distributed along side groups.
[0201] In the segmented copolymer composition, one or more chain extenders or crosslinkers (or reaction products thereof) may be present in a concentration of from about 0.01 wt% to about 25 wt%, such as from about 0.05 wt% to about 10 wt%.
[0202] The first soft segment can be based on the gross weight of the composition with a concentration of from about 5wt% to about 95wt%. In different embodiments, the first soft segment can be based on the gross weight of the composition with a concentration of about 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 95wt%. The second soft segment can be based on the gross weight of the composition with a concentration of from about 5wt% to about 95wt%. In different embodiments, the second soft segment can be based on the gross weight of the composition with a concentration of about 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 95wt%.
[0203] In certain embodiments, the fluorinated polyurethane oligomer is end-capped with a silane group. The end groups on the oligomer (in prepolymers) can be modified from isocyanates to silyl ethers. This can be achieved by the reaction of isocyanate-reactive silane species (e.g., aminopropyltriethoxysilane), to provide hydrolyzable groups well known in silicon and siloxane chemical reactions. This method eliminates the need to add a stoichiometric amount of a slaking agent to form a strongly associated hard segment, while replacing the slaking agent with a species having the ability to form a covalently cross-linked network under the influence of moisture or heat. It has been shown that this chemical reaction retains the beneficial aspects of urethane coatings while improving scratch resistance.
[0204] Furthermore, the reactivity of the terminal silane groups allows for additional functionality in the form of complementary silanes blended with the prepolymer mixture. Upon curing, the silanes are able to condense into a hydrolyzable network. This strategy allows for discrete domains with different compositions. Specific embodiments related to antifouling involve the combination of fluorinated urethane prepolymers terminated by silane reactive groups with additional alkyl silanes.
[0205] In some embodiments using segmented copolymers, the microstructure of the microphase separation containing the first and second soft segments can be characterized by an inhomogeneous microstructure. As expected in this patent application, "phase inhomogeneity", "inhomogeneous microstructure", etc. means that there is a multiphase microstructure in which there are at least two discrete phases separated from each other. For example, the two phases can be a discrete solid phase in a continuous solid phase, two co-continuous solid phases, or two discrete solid phases in a third continuous solid phase. The length scale of phase inhomogeneity can refer to the average size (e.g., effective diameter) of discrete inclusions of one phase dispersed in a continuous phase. The length scale of phase inhomogeneity can refer to the average center-to-center distance between the nearest neighbor inclusions of the same phase. The length scale of phase inhomogeneity can alternatively refer to the average separation distance between the nearest neighbor regions of a discrete (e.g., droplet) phase, where the distance traverses the continuous phase.
[0206] The average length scale of the phase inhomogeneity can generally be from about 0.1 micron to about 500 microns. In some embodiments, the average length scale of the phase inhomogeneity is from about 0.5 micron to about 100 microns, such as from about 1 micron to about 50 microns. In various embodiments, the average length scale of the phase inhomogeneity is about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, or 500 microns, including any intermediate values not explicitly recited, as well as ranges starting, ending, or including such intermediate values. These are average values, noting that a portion of the phase inhomogeneity may exist at length scales less than 0.1 micrometers or greater than 500 micrometers (e.g., about 1000 micrometers), with the overall average values falling within the range of 0.1-500 micrometers. It should be noted that in this disclosure, "about 0.1 micrometer" is intended to encompass 0.05-0.149 micrometers (50-149 nanometers), i.e., ordinary rounding.
[0207] Due to the scattering of light, the phase inhomogeneity typically results in an opaque coating or film. The scattering of light including visible wavelengths in the bulk of the material is controlled by the change in the refractive index of the medium through which it passes. Refractive index changes on a length scale near the wavelength of the propagating radiation will tend to scatter those wavelengths more effectively (Mie scattering), resulting in an opaque or white appearance of the coating. In the case of visible light with a wavelength range of about 400-700nm, a transparent or transparent coating typically must maintain a refractive index change of less than about 50nm in length. As the length scale of the phase inhomogeneity increases, the opacity of the material increases. Unless multiple phases happen to be refractive index matched, it is expected that phase inhomogeneities with an average length scale of from 0.1μm to 500μm will cause significant scattering in the material, resulting in an opaque structure with a thickness exceeding 25μm. See Althues et al., "Functional inorganic nanofillers for transparent polymers," Chem. Soc. Rev., 2007, 36, 1454-1465, which is hereby incorporated by reference for its teachings that materials with inhomogeneities below 50 nm will tend to be transparent, and materials with inhomogeneities above 50 nm (0.05 μm) will tend to be opaque.
[0208] In some embodiments, the antimicrobial structure is opaque with respect to ordinary light. In some embodiments, the antimicrobial structure is translucent or transparent with respect to ordinary light. In certain embodiments, the different phases of the antimicrobial structure are selected so that the corresponding refractive indices match or are substantially similar. One example is polytetrahydrofuran and poly(ethylene glycol), whose refractive indices match within about 1%. Another example is polytetrahydrofuran and poly(propylene glycol), whose refractive indices match within 2%. In some embodiments, the solid transmission material and the solid structural material are selected so that the refractive index of the solid structural material is within ±10%, preferably within ±5%, more preferably within ±2%, and most preferably within ±1%.
[0209] The antimicrobial structure can also be characterized by hierarchical phase separation. For example, when using segmented copolymers, in addition to being microphase separated, the first soft segment and the second soft segment are typically nanophase separated. As contemplated herein, two materials are "nanophase separated" meaning that the two materials are separated from each other at a length scale from about 1 nanometer to about 100 nanometers. For example, the nanophase separation length scale can be from about 10 nanometers to about 100 nanometers.
[0210] The nanophase separation between the first solid material (or phase) and the second solid material (or phase) may be caused by the presence of a third solid material (or phase) disposed between the regions of the first and second solid materials. For example, in the case where the first and second solid materials are soft segments of segmented copolymers also having hard segments, the nanophase separation can be driven by the intermolecular association of the dense hard segments of hydrogen bonding. In these cases, in some embodiments, the first soft segment and the hard segment are nanophase separated with an average nanophase separation length scale from about 10 nanometers to less than 100 nanometers. Alternatively, or additionally, the second soft segment and the hard segment can be nanophase separated with an average nanophase separation length scale from about 10 nanometers to less than 100 nanometers. The first and second soft segments themselves can also be nanophase separated with an average nanophase separation length scale (i.e., the length scale of a single polymer molecule) from about 10 nanometers to less than 100 nanometers.
[0211] Nanophase separation length scale is different from microphase separation length scale in level. For traditional phase separation in block copolymer, block is separated chemically at molecular level, and separation region on molecular length scale (such as nanophase separation length scale from about 10 nanometers to about 100 nanometers) is produced. Also see Petrovic et al., "POLYURETHANEELASTOMERS [polyurethane elastomer]" Prog.Polym.Sci. [Polymer Science Progress], Vol. 16, 695-836, 1991. The extreme difference of two soft segments means that in the reaction tank, the soft segments are not evenly mixed, and thus produce discrete regions rich in fluoropolymer or rich in non-fluoropolymer (e.g., PEG) components different from molecular level separation. These emulsion droplets contain a large amount of polymer chains, and therefore are within the range of micrometer length scale. These length scales withstand the curing process, so that the final material, in addition to molecular level (nanoscale) separation, also contains microphase separation formed by emulsion.
[0212] Thus, in some embodiments, the larger separation length scale (0.1-500 microns) is driven by an emulsification process that provides microphase separation in addition to classical molecular level phase separation. Chen et al., "Structure and morphology of segmented polyurethanes: 2. Influence of reactant incompatibility," POLYMER 1983, Vol. 24, pp. 1333-1340, which is hereby incorporated by reference for its teachings on microphase separation that can be produced by emulsification-based procedures.
[0213] In some embodiments, the discrete inclusions have an average particle size (e.g., effective diameter) from about 50 nm to about 150 μm, such as from about 100 nm to about 100 μm. In various embodiments, the discrete inclusions have an average particle size (e.g., effective diameter) of about 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 2 μm, 5 μm, 10 μm, 50 μm, 100 μm, or 200 μm.
[0214] In these or other embodiments, the discrete inclusions (solid structural phase) have an average center-to-center spacing between adjacent inclusions throughout the continuous matrix (continuous transport phase) of from about 50 nm to about 150 μm, such as from about 100 nm to about 100 μm. In various embodiments, the discrete inclusions have an average center-to-center spacing between adjacent inclusions of about 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 2 μm, 5 μm, 10 μm, 50 μm, 100 μm, or 200 μm.
[0215] In some variations of the present invention, the antimicrobial structure forms a coating disposed on a substrate. For example, the coating can have a thickness from about 1 μm to about 10 mm. In various embodiments, the coating thickness is about 100 nm, 1 μm, 10 μm, 100 μm, 1 mm, or 10 mm. The benefit provided by a thicker coating is that the coating can still function even after surface wear because the entire depth of the coating (not just the outer surface) contains functional materials. The coating thickness will generally depend on the specific application.
[0216] An optional substrate can be disposed on the back side of the antimicrobial structure. A substrate will be present when the material forms a coating or a portion of a coating (e.g., a layer of a multilayer coating). Many substrates are possible, such as metal, polymer, wood, or glass substrates. Essentially, the substrate can be any material or object that requires antimicrobial protection.
[0217] In some embodiments, an adhesion layer is disposed on a substrate, wherein the adhesion layer is configured to promote adhesion of the antimicrobial structure to a selected substrate. The adhesion layer comprises one or more adhesion promoting materials, such as, but not limited to, primers (e.g., carboxylated styrene-butadiene polymers), alkoxysilanes, zirconates, and titanium alkoxides.
[0218] As will be appreciated by those skilled in the art, various strategies may be employed to form the material of the antimicrobial structure.
[0219] In some embodiments, the antimicrobial structure is in the form of a patch that can be adhered to a surface during use.
[0220] Before forming the final antimicrobial structure, a precursor composition can be provided. The precursor composition can be aqueous, solvent-based, or a combination thereof. For example, in some aqueous embodiments, the first or second soft segment can be derived from an aqueous dispersion of a linear crosslinkable polyurethane containing a charged group, and the other soft segment can be derived from a crosslinking agent containing a charged group.
[0221] In some embodiments, the precursor includes a silane, a silyl ether, a silanol, an alcohol, or a combination or reaction product thereof, and optionally further includes a protecting group that protects the precursor from reaction with other components.
[0222] Some embodiments use waterborne polyurethane dispersions. Successful waterborne polyurethane dispersions sometimes require specific components to contain ionic groups to help stabilize the emulsion. Other factors that contribute to the preparation of stable dispersions include the concentration of ionic groups, the concentration of water or solvent, and the addition and mixing rate of water during the conversion process. The isocyanate prepolymer can be dispersed in water. Subsequently, the curing agent component can be dispersed in water. Then water evaporation promotes the formation of a microphase-separated polyurethane material.
[0223] The composition or precursor composition can generally be formed from a precursor material (or combination of materials) provided, obtained, or manufactured by the starting components. The precursor material can be hardened or cured in some manner to form a precursor composition containing a first soft segment and a second soft segment that are microphase separated at a microphase separation length scale from about 0.1 micrometers to about 500 micrometers. The precursor material can be, for example, a liquid; a multiphase liquid; a multiphase slurry, emulsion, or suspension; a gel; or a dissolved solid (in a solvent).
[0224] In some embodiments, based on the incompatibility between the two blocks (e.g., PEG and PFPE), an emulsion is formed in the reaction mixture. The emulsion provides microphase separation in the precursor material. The precursor material is then cured by casting or spraying. The microphase separation withstands the curing process (even if the length scale changes slightly during the curing process), thereby providing the benefits of the final material (or precursor composition) as described herein. Without being limited by theory, the microphase separation in the present invention is independent of the molecular length scale separation (5-50nm) shown by many traditional block copolymer systems. On the contrary, the larger length scale (i.e., 0.1-500 μm) of the microphase separation is caused by the emulsion formed before curing.
[0225] Xu et al., "Structure and morphology of segmented polyurethanes: 1. Influence of incompatibility on hard-segment sequence length," POLYMER 1983, Vol. 24, pp. 1327-1332 and Chen et al., "Structure and morphology of segmented polyurethanes: 2. Influence of reactant incompatibility," POLYMER 1983, Vol. 24, pp. 1333-1340, are each hereby incorporated by reference herein for their teachings regarding emulsion formation in polyurethane systems prior to curing.
[0226] In some variations of the invention, a precursor material is applied to a substrate and reacted, cured or hardened to form a final composition (e.g., a coating). In some embodiments, a precursor material is prepared and then dispensed (deposited) onto an area of interest. Any known method can be used to deposit the precursor material. Fluid precursor materials allow for convenient dispensing using spraying or casting techniques.
[0227] The fluid precursor material can be applied to the surface using any coating technique, such as, but not limited to, spraying, dipping, blade coating, air knife coating, curtain coating, single and multilayer slide coating, gap coating, knife-on-roll coating, metering rod (Meyer rod) coating, reverse roll coating, rotary screen coating, extrusion coating, casting, or printing. Because relatively simple coating methods can be used, rather than photolithography or vacuum-based techniques, the fluid precursor material can be quickly sprayed or cast as a thin layer over a large area (e.g., several square meters).
[0228] When a solvent or carrier fluid is present in the fluid precursor material, the solvent or carrier fluid may include one or more compounds selected from the group consisting of water, alcohols (e.g., methanol, ethanol, isopropanol, or tert-butyl alcohol), ketones (e.g., acetone, methyl ethyl ketone, or methyl isobutyl ketone), hydrocarbons (e.g., toluene), acetates (e.g., tert-butyl acetate), acids (e.g., organic acids), bases, and any mixtures thereof. For example, when a solvent or carrier fluid is present, it may be in a concentration of from about 10 wt % to about 99 wt % or more.
[0229] Precursor materials can be converted into intermediate materials or final compositions using any one or more curing or other chemical reactions, or separations (such as removal of solvents or carrier fluids, monomers, water, or steam). Curing refers to the toughening or hardening of polymer materials achieved by physical crosslinking, covalent crosslinking, and / or covalent bonding of polymer chains assisted by electromagnetic waves, electron beams, heat, and / or chemical additives. Chemical removal can be achieved by heating / flash evaporation, vacuum extraction, solvent extraction, centrifugation, etc. For example, physical conversion can also be involved to transfer precursor materials to a mold. If necessary, additives can be introduced during the curing process to adjust pH, stability, density, viscosity, color, or other characteristics for function, decoration, safety, or other reasons.
[0230] Examples
[0231] Example 1: Synthesis of polymeric antimicrobial structures.
[0232] Combine polyethylene glycol (M n =400g / mol, 9.88g), fluoropolymer Fluorolink E10H (M n =1800g / mol, 10.0g), polyisocyanate Desmodur 3300 (equivalent weight = 193, 9.54g) and dibutyltin dilaurate (2000ppm). The ratio of polyethylene glycol and fluoropolymer was adjusted to produce a ratio of 60vol% / 40vol%. This mixture was then placed in a centrifugal mixer (2min, 2000rpm) and homogenized. The resin was then cast on a biaxially oriented polyethylene terephthalate (Mylar) with a release film using a doctor blade and cured at room temperature.
[0233] Example 2: Synthesis of polymeric antimicrobial structures.
[0234] Combine poly(tetramethylene glycol) (M n =650 g / mol, 10.00 g) (also known as polyTHF or pTHF), polyethylene glycol (M n =600g / mol, 3.81g) (also known as PEG), polyisocyanate Desmodur 3300 (equivalent weight = 193, 8.39g) and dibutyltin dilaurate (2000ppm). The ratio of poly(tetramethylene glycol) and polyethylene glycol was adjusted to produce a 75vol% / 25vol% ratio, respectively. This mixture was then placed in a centrifugal mixer (2min, 2000rpm) and homogenized. The resin was then cast on Mylar with a release film using a doctor blade and cured at room temperature.
[0235] Example 3: Electrochemical impedance spectroscopy (EIS) of antimicrobial agent transport in polymer films.
[0236] Electrochemical impedance spectroscopy (EIS) was used to measure the transport rate of a selected antimicrobial agent (10% benzalkonium chloride in water) in a series of PEG-polyTHF membranes. The typical membrane surface area was 1.08 cm 2 , with a thickness of about 0.02 cm. In a two-electrode electrochemical cell, 2 With 5×10 6 Measure frequencies between Hz.
[0237] Figure 4 The magnitude of the impedance spectra (normalized by membrane thickness) of six membranes with different PEG concentrations (0 vol%, 25 vol%, 40 vol%, 50 vol%, 60 vol% and 75 vol% PEG, the remainder being pTHF) after being immersed in a 10% benzalkonium chloride (in water) solution for about 2 days is shown. For comparison, the normalized impedance spectrum of a pure solution of 10% benzalkonium chloride in water is also shown. Figure 4 Here, “quat” refers to 10% benzalkonium chloride. The specific conductivity and diffusion coefficient are given by 4 Impedance measurement at Hz ( Figure 4 ).
[0238] Figure 5 The graphs show the specific conductivity (left axis) and diffusion coefficient (right axis) as a function of PEG concentration (0 vol%, 25 vol%, 40 vol%, 50 vol%, 60 vol% and 75 vol%) after immersion in a 10% benzalkonium chloride (in water) solution for about 2 days. The conductivity and diffusion coefficient were determined by impedance at 10 kHz. Figure 5 The dashed line near the top shows the conductivity and diffusion coefficient of a pure solution of 10% benzalkonium chloride in water.
[0239] The specific conductivity of benzalkonium chloride in the membrane with 25 vol% PEG was about 400× higher than that of pure pTHF membrane. This measurement indicates that a small amount of transport phase (e.g., PEG) is sufficient to achieve rapid transport of benzalkonium chloride in these membranes. The transport rate (conductivity) of benzalkonium chloride increases with PEG concentration, increasing an additional 30× at 75 vol% PEG.
[0240] Example 4: Use of antimicrobial structures.
[0241] This example illustrates an antimicrobial structure and a commercial method of using the antimicrobial structure. The structure and method of using the same are not intended to limit the scope of the invention in any way.
[0242] The antimicrobial structure is made of a discrete solid structural phase of perfluoropolyether, a continuous transport phase of poly(ethylene oxide) and optionally polyacrylic acid and / or 2-phenoxyethanol electrolyte, a trifunctional isocyanate as a crosslinker to lock into the network structure, and a quaternary ammonium biocide as an antimicrobial agent.
[0243] A shared vehicle (e.g., a taxi) incorporates the disclosed antimicrobial structure as a seat coating. A first passenger enters the vehicle and removes a portion of the antimicrobial agent on the surface during entry. Less than an hour later, a second passenger coughs and deposits a certain amount of active virus on the seat surface. Due to the rapid transmission from the continuous transmission phase, the seat surface is quickly and automatically replenished with antimicrobial agent (quaternary ammonium biocide) according to the principles set forth in the present disclosure. The antimicrobial agent inactivates the virus from the second passenger. Less than an hour later, a third passenger enters the same shared vehicle and contacts the same surface, but the third passenger is not infected because the viral load on the seat surface has been reduced to a very low level that no longer infects humans.
[0244] In this detailed description, reference has been made to a number of embodiments and drawings in which specific exemplary embodiments of the invention are shown by way of illustration. These embodiments are described in sufficient detail to enable those skilled in the art to practice the invention, and it should be understood that those skilled in the art may make modifications to the various embodiments disclosed.
[0245] When the above method and steps indicate that certain events occur in a certain order, those of ordinary skill in the art will recognize that the order of certain steps can be modified, and such modification is carried out according to variants of the present invention. In addition, certain steps can be carried out simultaneously by parallel processes when possible, or can be carried out successively.
[0246] All publications, patents, and patent applications cited in this specification are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually set forth herein.
[0247] The above-described embodiments, variations, and accompanying drawings should provide an indication of the practicality and versatility of the present invention. Other embodiments that do not provide all of the features and advantages set forth herein may also be used without departing from the spirit and scope of the present invention. Such modifications and variations are considered to fall within the scope of the present invention as defined by the claims.
Claims
1. An antimicrobial structure comprising: (a) a solid structural phase comprising a solid structural material, wherein the solid structural material comprises a solid structural polymer, wherein the solid structural polymer is selected from the group consisting of non-fluorinated carbon-based polymers, silicones, fluorinated polymers, and combinations thereof; and (b) a continuous transport phase dispersed in the solid structured phase, wherein the continuous transport phase comprises (i) an electrolyte salt; (ii) a transport phase liquid; (iii) a polymer host as a solid transport material, wherein the solid transport material comprises a hygroscopic solid transport polymer, a hydrophobic and non-oleophobic solid transport polymer, a hydrophilic solid transport polymer having an ionic charge, or an electrolyte solid transport polymer; and (iv) an antimicrobial agent, wherein the transport phase liquid at least partially dissolves the antimicrobial agent, wherein the solid transport material and the antimicrobial agent form a solution, and The solid structural phase and the continuous transport phase are separated by an average phase separation length ranging from 100 nanometers to 500 micrometers.
2. The antimicrobial structure of claim 1, wherein: The non-fluorinated carbon-based polymer is selected from the group consisting of polyalkanes, polyurethanes, polyethers, polyureas, polyesters, and combinations thereof.
3. The antimicrobial structure of claim 1, wherein: The silicone is selected from the group consisting of polydimethylsiloxane, polytrifluoropropylmethylsiloxane, polyaminopropylmethylsiloxane, polyaminoethylaminopropylmethylsiloxane, polyaminoethylaminoisobutylmethylsiloxane, and combinations thereof.
4. The antimicrobial structure of claim 1, wherein: The fluorinated polymer is selected from the group consisting of fluorinated polyols, perfluorocarbons, perfluoropolyethers, polyfluoroacrylates, polyfluorosilicones, polyvinylidene fluoride, polytrifluoroethylene, and combinations thereof.
5. The antimicrobial structure of claim 1, wherein: The hygroscopic solid transport polymer is selected from the group consisting of polyacrylic acid, polyethylene glycol, poly(2-hydroxyethyl methacrylate), poly(vinyl imidazole), poly(2-methyl-2-oxazoline), poly(2-ethyl-2-oxazoline), poly(vinyl pyrrolidone), modified cellulose polymers, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, and combinations thereof.
6. The antimicrobial structure of claim 1, wherein: The hydrophobic and non-oleophobic solid transfer polymer is selected from the group consisting of polypropylene glycol, polytetramethylene glycol, polybutadiene, polycarbonate, polycaprolactone, acrylic polyol, and combinations thereof.
7. The antimicrobial structure of claim 1, wherein: In the hydrophilic solid transport polymer having ionic charges, the ionic charges are present in the hydrophilic solid transport polymer as carboxylate groups, amine groups, sulfate groups, or phosphate groups.
8. The antimicrobial structure of claim 1, wherein: The electrolyte solid transport polymer is selected from the group consisting of polyethylene oxide, polypropylene oxide, polycarbonate, polysiloxane, polyvinylidene fluoride, and combinations thereof.
9. The antimicrobial structure of claim 1, wherein: The solid structural material is a solid structural polymer, wherein the solid transport material is a solid transport polymer, and wherein the solid structural polymer is cross-linked with the solid transport polymer via cross-linking molecules.
10. The antimicrobial structure of claim 9, wherein: The cross-linking molecule comprises at least one moiety selected from the group consisting of an amine moiety, a hydroxyl moiety, an isocyanate moiety, and combinations thereof.
11. The antimicrobial structure of claim 1, wherein: The transport phase liquid is selected from the group consisting of water, dialkyl carbonate, propylene carbonate, γ-butyrolactone, 2-phenoxyethanol, and combinations thereof.
12. The antimicrobial structure of claim 1, wherein: The transport phase liquid is selected from ionic liquids.
13. The antimicrobial structure of claim 1, wherein: The transport phase liquid comprises one or more water-soluble salts, and wherein optionally at least one of the water-soluble salts acts as the antimicrobial agent.
14. The antimicrobial structure of claim 13, wherein: The water-soluble salt is selected from the group consisting of copper chloride, copper nitrate, zinc chloride, zinc nitrate, silver chloride, silver nitrate, and combinations thereof.
15. The antimicrobial structure of claim 1, wherein: The transport phase liquid is a eutectic liquid salt, and wherein the eutectic liquid salt is optionally derived from an ammonium salt.
16. The antimicrobial structure of claim 15, wherein: The eutectic liquid salt contains the antimicrobial agent.
17. The antimicrobial structure of claim 1, wherein: The antimicrobial agent is selected from quaternary ammonium molecules.
18. The antimicrobial structure of claim 1, wherein: The antimicrobial agent is selected from N-halamines.
19. The antimicrobial structure of claim 1, wherein: The antimicrobial agent is selected from oxidizing molecules, and wherein the oxidizing molecules are optionally selected from the group consisting of sodium hypochlorite, hypochlorous acid, hydrogen peroxide, and combinations thereof.
20. The antimicrobial structure of claim 1, wherein: The antimicrobial agent is selected from metal ions, and wherein the metal ions are optionally selected from the group consisting of silver, copper, zinc, and combinations thereof.
21. The antimicrobial structure of claim 1, wherein: The antimicrobial structure is characterized in that in the continuous transport phase, the antimicrobial agent has a relative humidity of 10 -16 m 2 / s and 10 -9 m 2 / s diffusion coefficient.
22. The antimicrobial structure of claim 1, wherein: The antimicrobial structure contains embedded electrodes, and wherein the antimicrobial agent is electrically or electrochemically rechargeable.
23. The antimicrobial structure of claim 1, wherein: The antimicrobial structure further comprises one or more protective layers.
24. The antimicrobial structure of claim 1, wherein: The antimicrobial structure is a coating or is present in a coating.
25. The antimicrobial structure of claim 1, wherein: The antimicrobial structure is present on the surface of the bulk object.
Citation Information
Patent Citations
Contact-killing, QAC functionalized thermoplastic polyurethane for catheter applications
US20190106525A1
Non-leaching surface-active film compositions for microbial adhesion prevention
CN101374607A
Multiphase coatings with separated functional particles, and methods of making and using the same
US20190048223A1